Diverse impacts of a step and repeated BDE209-Pb exposures on accumulation and metabolism of BDE209 in earthworms. (September 2016) - Zhang, Wei; Liang, Jun; Li, Jing; Lin, Kuangfei; Fu, Rongbing
Abstract: Decabromodiphenyl ether (BDE209) and lead (Pb) are the two common contaminants at e-waste recycling sites (EWRSs). A laboratory incubation study was conducted to explore the impacts of a step and repeated BDE209-Pb exposures on accumulation and metabolism of BDE209 in earthworms Eisenia fetida for the first time. The results indicated that BDE209 concentrations in repetitively-polluted soils were clearly higher. And the existence of high-level Pb could promote the bioaccumulation of BDE209 in earthworms along the exposure time. The post-clitellum contents of BDE209 were more than the pre-clitellum during the entire incubation. Additionally, GC/MS analysis results demonstrated that BDE206, BDE208, BDE153, BDE99, BDE47 and BDE28 could be detected in Eisenia fetida throughout 28-d experiment, and BDE206 and BDE208 were predominant metabolic products. A step exposure decreased the capability to metabolize BDE209 in the presence of Pb. Average bioaccumulation factor (BAF) for a step treatment was 0.525, as well as it was more than 1.1 times that of repeated exposure (BAF = 0.48). SEM observations suggested that a step exposure mode aggravated the damage in earthworms than repeated exposure. The results and related findings will establish a useful scientific basis for soil ecological risk assessment at EWRSs. Highlights: The presence of high-level Pb could promote the bioaccumulation of BDE209 in earthworms. A step persistent exposure aggravated the damage in earthworms more than a repeated exposure. A step exposure decreased the capability of earthworms to metabolize BDE209 in the presence of Pb. BDE209 accumulation in post-clitellum was higher than that in pre-clitellum.